An Analysis of Directive Speech Acts In Anime “Oregairu” by Wataru Watari - Aini, Zuhratul; Junaidi, Abdul Majid (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the form of directive speech acts and their functions in the anime Oregairu by Wataru Watari. Therefore, this study is expected to be useful in illustrating the directive phenomenon. This research method is qualitative research and the main data source of this study is the complete script of the anime Oregairu by Wataru Watari. This study uses observation and documentation techniques in collecting data. The researcher analyzed the data using Miles and Huberman’s theory, namely data collection, data reduction, data display and conclusion. This study has two objectives. The first objective is to describe the form of directive speech acts in the dialogue of the anime film Oregairu by Wataru Watari. The second objective is to determine the function of directive speech acts in the dialogue of the Anime Film Oregairu by Wataru Watari. The results of this study are related to directive speech acts seen from the aspects of form and function. In the dialogue of Anime Oregairu by Wataru Watari, six forms of directive speech acts are found, namely orders, requests, solication, prohibitions, advice and criticism. Judging from the function of directive speech acts, the dialogue of the Anime film Oregairu by Wataru Watari has various functions. The form of directive speech acts of commands has the functions of commanding, ordering, directing, forcing and requiring. The form of directive speech acts of requests has the functions of asking, begging, expecting and offering. The form of directive speech acts of invitations has the functions of inviting, pushing, seducing and challenging. The form of directive speech acts of prohibitions has the functions of prohibiting and preventing. The form of directive speech acts of advice has the functions of suggesting, appealing and reminding. The form of directive speech acts of criticism has the functions of criticism, satire, swearing and anger.